2014
DOI: 10.1021/sc500507b
|View full text |Cite
|
Sign up to set email alerts
|

Selective Conversion of Glucose into Lactic Acid with Transition Metal Ions in Diluted Aqueous NaOH Solution

Abstract: An efficient process for the selective conversion of glucose to lactic acid with transition metal ions in diluted aqueous NaOH solution under alkaline hydrothermal conditions was investigated. As a result, Ni2+ was found to be efficient in the production of lactic acid from glucose and decreased simultaneously the NaOH concentration. The highest yield of 25% for lactic acid was achieved with 0.01 M Ni2+, 0.01 M NaOH, and 35% water filling at 300 °C for 1 min. In addition, our results suggest that the role of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…e hydrothermal process, one of the most potential approaches, is used in the conversion of biomass into valuable resources, since water can serve as a reaction medium bearing special properties when treated in the high temperature and pressure [26]. With respect to the issue of catalytic transformation of biomass into LA with the hydrothermal process using alkaline catalysts, Jin research group made many valuable contributions to this research theme [26][27][28][29][30][31][32][33][34]. Initially, they demonstrated that glycolaldehyde, an aldose with two carbon atoms, usually produced via reverse aldol condensation of C 6 sugars, can also generate LA with 28% yield using 0.75 M·NaOH basic catalyst (300°C, 10 min) [26].…”
Section: Alkaline Catalytic Manners For Lamentioning
confidence: 99%
“…e hydrothermal process, one of the most potential approaches, is used in the conversion of biomass into valuable resources, since water can serve as a reaction medium bearing special properties when treated in the high temperature and pressure [26]. With respect to the issue of catalytic transformation of biomass into LA with the hydrothermal process using alkaline catalysts, Jin research group made many valuable contributions to this research theme [26][27][28][29][30][31][32][33][34]. Initially, they demonstrated that glycolaldehyde, an aldose with two carbon atoms, usually produced via reverse aldol condensation of C 6 sugars, can also generate LA with 28% yield using 0.75 M·NaOH basic catalyst (300°C, 10 min) [26].…”
Section: Alkaline Catalytic Manners For Lamentioning
confidence: 99%
“…In contrast, catalytic processes to produce lactic acid offer high reactionr ates and simple separation of products. [16] Moreover,t he formation of lactic acid salt in alkaline condition makes the separation and purification of lactic acid more difficult. [4,11] This retro-aldol condensation has typicallyb een renderedb ya lkaline conditions, but faces problemso fl ow yield and selectivity for lactic acid with side products including formic acid, malonic acid, and acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Sels and co-workers reported a6 0% yield of total esters from cellulose catalyzed by tin triflate in methanola t2 00 8Ca fter 4h. [14][15][16] Sels and co-workers reported a6 0% yield of total esters from cellulose catalyzed by tin triflate in methanola t2 00 8Ca fter 4h.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations